Prototipe Sistem Monitoring Dan Otomatisasi Penerangan Jalan Umum Tenaga Surya Berbasis IOT Sebagai Media Pembelajaran Di Politeknik Penerbangan Medan - Xecillia Roulina Ritonga; Usman Usman; Ferry Budi Cahyono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to design and develop a prototype of a monitoring and automation system for solar-powered public street lighting (PJUTS) based on IoT at Medan Aviation Polytechnic. The system is designed to address several common issues faced by PJUTS, such as battery damage, undetected lamp outages, and the lack of a remote monitoring system. The method used is Design and Development (D&D), which includes the design, development, and testing of the system. The developed prototype uses a BH1750 sensor to measure light intensity, an INA219 sensor to monitor voltage and current, and an LDR sensor to control lamp automation. The generated data can be displayed locally on an LCD and sent to the Blynk application for remote monitoring. The test results show that the system can monitor lux values and lamp conditions in real-time, as well as measure and display the current, voltage, and power of the battery during operation. The system also successfully automates the operation of PJUTS lamps, optimizing the use of solar energy efficiently. This prototype not only enhances the operational efficiency and sustainability of PJUTS but also contributes to the development of IoT technology and renewable energy systems as a learning tool at Medan Aviation Polytechnic.